2011
DOI: 10.4236/jmmce.2011.1014104
|View full text |Cite
|
Sign up to set email alerts
|

Wear Characteristics in Al-SiC Particulate Composites and the Al-Si Piston Alloy

Abstract: ABSTRACT:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The wear rates of material fabricated by vortex method decrease less rapidly than the materials prepared by dilution material with increase in SiC volume fraction and applied load. Similar studies on wear behaviour of Al-SiC composite have also been reported by other researchers [22,23].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The wear rates of material fabricated by vortex method decrease less rapidly than the materials prepared by dilution material with increase in SiC volume fraction and applied load. Similar studies on wear behaviour of Al-SiC composite have also been reported by other researchers [22,23].…”
Section: Introductionsupporting
confidence: 89%
“…For example, the interaction V × L occupies columns 3 and 4, and for trial no 1, the cell fields show 1 in column 3 and 1 in column 4. Thus V × L has the value 11 which means it is the combination of level 1 of V and level 1 of L. Similarly there are 9 such combinations(11,22, 33,12,21,23, 32,13, and 31) for V × L interaction in columns 3 and 4. A similar procedure applies to other interaction terms as well.…”
mentioning
confidence: 99%
“…[18][19][20]27,33,34,[69][70][71][72][73][74][75][76][77][78][79][80]. In the case of composites, additional factors controlling the wear behaviour are morphology, mode of distribution and content of dispersoid phase and the nature of dispersoid/matrix bonding [2,6,19,20,22,27,28,34,39,45,70,71,76,79,[81][82][83][84][85][86][87][88][89][90]. Experimental parameters include applied load, traversal distance, speed etc.…”
Section: Bk Prasad Et Al Two-body Abrasive Wear Behaviour Of In-simentioning
confidence: 99%
“…This was due to the presence of hard SiC and B4C nanoparticulates which restricted the flow of material under the applied load. In addition, the worn surface of the nanocomposites has higher hardness and hence the ploughing tendency of the hard asperity of the counter face was less compared to the soft matrix alloy [12,33,34]. …”
Section: Friction Coefficient Vs Normal Loadmentioning
confidence: 99%